Testosterone Deficiency, Cardiac Health, and Older Men - G. Hackett; M. Kirby; A. J. Sinclair (International Journal of Endocrinology)
Low levels of testosterone are manifested by erectile dysfunction, reduced sexual desire, and loss of morning erections with increasing numbers of men are being diagnosed and require treatment. The prevalence rates of testosterone deficiency vary according to different studies but may be as high as 40% in populations of patients with type 2 diabetes. There is increasing evidence that testosterone deficiency is associated with increased cardiovascular and all-cause mortality. Screening for low testosterone is recommended in a number of high risk groups including those with type 2 diabetes and metabolic syndrome. There are recent data to suggest that testosterone replacement therapy may reduce cardiovascular mortality as well as improving multiple surrogate markers for cardiovascular events. Specific clinical trials of testosterone replacement therapy are needed in selected populations but in the meantime we must treat patients based on the best current evidence.